THE EFFECT OF INSTITUTIONAL OWNERSHIP, FOREIGN OWNERSHIP, LEVERAGE AND AUDIT FIRM SIZE ON CSR DISCLOSURE - Febryanti, Imanuela Glory Della; Suhendah, Rousilita (Graduate Program of Universitas Tarumanagara, 2024)
This study empirically examines the effect of institutional ownership structure, foreign ownership structure, financial leverage and audit firm size from 2019-2021. The dependent variables used in this study are corporate social responsibility disclosure. This study uses quantitative research methods with secondary data obtained from the annual financial statements of basic material companies listed on the BEI. There are 138 data from 46 companies selected as research samples based on the purposive sampling method. The data processing in this study was tested using the Eviews 10. The results of the regression test showed that institutional ownership had a positive and significant effect on corporate social responsibility disclosure (CSRD), while foreign ownership, financial leverage and audit firm size had no effect on corporate social responsibility disclosure (CSRD).